1973
DOI: 10.1063/1.1679339
|View full text |Cite
|
Sign up to set email alerts
|

Nonempirical LCAO MO SCF studies of the group IIa dihalides BeF2, MgF2, and CaF2

Abstract: Nonempirical LCAO MO SCF calculations are reported for the ground, C 2 " states of the Group IIa dihalides, BeF 2 , MgF2' and CaF 2 . These calculations demonstrate the importance of 3d orbitals in the bonding trends of the dihalides and, hence, in the determination of the equilibrium bond angles and the bending force constants. The calculations on BeF 2 indicate that d orbitals play an important role in the bonding but do not preferentially alter the general features of the total energy curve at any bond angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 26 publications
6
27
0
Order By: Relevance
“…This also leads to an increase in valence angle. It is not surprising, therefore, that in CaF2 the experimental angle is 141 0 [7], and that a recent Stark effect study of gaseous BaCh [14] leads to an angle < 135 0 • These values are quite in keeping with our general theory.…”
Section: Tile Hybridization or Valence-state Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…This also leads to an increase in valence angle. It is not surprising, therefore, that in CaF2 the experimental angle is 141 0 [7], and that a recent Stark effect study of gaseous BaCh [14] leads to an angle < 135 0 • These values are quite in keeping with our general theory.…”
Section: Tile Hybridization or Valence-state Modelsupporting
confidence: 84%
“…There is clearly no possible chance that any dihalide of these atoms should be nonlinear. Finally we may compare our general theory with the particular calculations of Gole et al [7]. These authors showed that in MgF2 and CaF2 the inclusion of d orbitals in the basis set tended to favor a bent conformation, and in CaF2 succeeded in making this more stable than the linear conformation.…”
Section: Tile Hybridization or Valence-state Modelmentioning
confidence: 58%
See 1 more Smart Citation
“…This molecule is an example of a non linear dihalide. Theoretical investigations have also been reported in the literature [4].…”
Section: Introductionmentioning
confidence: 95%
“…The failure of the VSEPR model and Walsh's rules to predict these bent structures prompted the development of improved models. Two physical models, d-orbital participation [22][23][24][25][26][27][28][29][30][31] and core polarization, 11,12,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] were used to explain these unexpected bent structures and have been discussed in detail in the reviews by Hargittai 2 and Kaupp. 46 In the d-orbital participation model, the lighter metals ͑e.g., Be and Mg͒ have only valence ns and np orbitals for covalent bonding leading to sp hybridization, which results in a linear structure.…”
Section: Introductionmentioning
confidence: 99%